Italia y Estados Unidos: nacionalismo vs. migración ; Italy and the United States: nationalism vs. migration - Núñez García, Silvia (2022)
El propósito de este artículo es aportar una aproximación crítica a los liderazgos políticos de Matteo Salvini en Italia y de Donald Trump en los Estados Unidos, haciendo énfasis en la convergencia entre ambos en el tratamiento excluyente de la migración indocumentada. A través de un enfoque cualitativo, se aborda una cadena de acontecimientos que persiguen conectar la implementación de políticas anti-inmigrantes a una narrativa vertical, obcecada con el regreso al pasado y la exacerbación del nacionalismo en ambos países. En la construcción de este imaginario se revisa someramente el rol estratégico de las redes sociales. The purpose of this article is to provide a critical approach to the political leadership of Matteo Salvini in Italy and Donald Trump in the United States, emphasizing the convergence between them both in the exclusionary treatment of undocumented migration. Through a qualitative methodology, bibliographic sources—mostly digital—were selected to analyze a chain of events that seek to connect the implementation of anti-immigrant policies to a vertical narrative, obsessed with the return to the past and the exacerbation of nationalism in both countries. The technique used is based on the realistic approach in International Relations, which allows us to note as an anthropological premise that if human beings pursue his own benefit, in this case the conclusion will lead to confirm this assumption in the actions of the leaders studied here. In the construction of the political imaginary of both characters, the strategic role of social networks is also briefly reviewed.